Influence of Nb addition on the structure, microstructure, Vickers microhardness, and Young's modulus of new β Ti-xNb-5Mo alloys system - Cardoso, Giovana Collombaro [UNESP]; Kuroda, Pedro Akira Bazaglia; Grandini, Carlos Roberto [UNESP] (Elsevier, 2023)
New Ti alloys are being developed to obtain materials with better properties for biomedical applications. In order to avoid complications caused for the presence of Al and V ions in the blood stream, novel alloys have been developed without these two elements. Mo and Nb are two non-toxic β-stabilizing elements used in Ti alloys because they decrease the elastic modulus and improve corrosion resistance. Thus, this study investigated the influence of Nb addition in Ti-xNb-5Mo alloy (x = 0, 10, 20, 30 %wt) on microstructure, structure, and selected mechanical properties. The samples were characterized after annealing, and the results showed the decrease of α phase and growth of β phase with the addition of Nb. The ω phase in the alloy containing 20% Nb was also detected. The samples’ elastic modulus and microhardness tended to decrease with increasing of the β phase, except for the Ti–20Nb–5Mo alloy due to phase hardening ω. The average crystallite size of the α and β phases increased with the addition of Nb.
Keywords: Biomaterials; Microstructural analyses; Molybdenum; Niobium; Ti alloys; Vickers microhardness; Young's modulus